Women's participation in panchayati raj : nature and effectiveness, a Northern India perspective - Singla, Pamela (Jaipur : Rawat Publications, 2007)
Study with special reference to Haryana, India.
Includes bibliographical references (p. [274]-281) and index.
Keywords: WOMAN-INDIA; PANCHAYATI-INDIA